Application of aquaponics technology with different substrate combinations on water quality and growth of tilapia (Oreochromis niloticus) - Jannah, Miftahul; Zulpikar, Zulpikar; Muliani, Muliani (Universitas Malikussaleh, 2021)
Tilapia (Oreochromis niloticus) is a type of freshwater fish that is widely cultivated by Indonesians. The problem that often arises in cultivation is lack of water quality. One of the ways to improve water quality is by using aquaponics technology, which can help to overcome lack of water quality by using a combination of different sub-extracts. This study was aim to determine the effect of different substrate combinations on water quality, growth of tilapia (Oreochromis niloticus) and lettuce vegetables. This study used an experimental method with a completely randomized design (CRD) with 4 treatments and 3 replications. That was control, rockwool and sawdust, rockwool and charcoal, rockwool and husk charcoal. The results showed that the use of different substrate combinations had no significant effect on water quality and fish growth. The best water quality was found in treatment D (rockwool and husk charcoal) with ammonia content of 0.09 mg / L, nitrate 13.45 mg / L, temperature 28.84 0c, pH 7.29 and DO 5.75 mg / L.Keywords: aquaponic system; substrate; tilapia; water quality.